ESTIMASI BEBAN PENCEMAR ORGANIK DARI KEGIATAN DOMESTIK DI BAGIAN HILIR SUNGAI CILIWUNG - Fanny Novia; Ahda Silmi (ENVIROSAN : Jurnal Teknik Lingkungan, 2019)
Discharge of untreated domestic wastewater can contribute to water body pollution. Research was conducted to calculate organic wastewater loading of biochemical oxygen demand (BOD) and chemical oxygen demand (COD) loaded to downstream of Ciliwung River segment 5 and 6. Calculation of organic wastewater loading used indirect method by using emission factor and total of population. The results showed amount of organic wastewater loading in downstream of Ciliwung River is increasing year by year. The amount of BOD loading in segment 5 and 6 from 2014 to 2016 was 27.166,41 ton/year, 27.440,97 ton/year dan 29.490,21 ton/year. The amount of COD loading in segment 5 and 6 from 2014 to 2016 was 61.939,42 ton/year, 62.565,42 ton/year, 67.237,68 ton/year. Daily amount of BOD dan COD loading in segment 5 and 6 was 0,08 kg BOD/day and 0,17 kg COD/day. To meet requirement of wastewater standard, domestic wastewater has to be treated to decrease BOD and COD loading with efficiency for each parameters are ± 96 % dan ± 94 % Keywords: water quality, wastewater loading, BOD, COD, Ciliwung River